Some Insights to the Reuse of Dredged Marine Soils by Admixing with Activated Steel Slag - Chee-Ming Chan; Ainun Nazhirin Abdul Jalil (Advances in Civil Engineering)
Regular dredging is necessary for the development of coastal regions and the maintenance of shipping channels. The dredging process dislodges sediments from the seabed, and the removed materials, termed dredged marine soils, are generally considered a geowaste for dumping. However, disposal of the dredged soils offshores can lead to severe and irreversible impact on the marine ecosystem, while disposal on land often incurs exorbitant costs with no guarantee of zero-contamination. It is therefore desirable to reuse the material, and one option is solidification with another industrial waste, that is, steel slag. This paper describes the exploratory work of admixing dredged marine soil with activated steel slag for improvement of the mechanical properties. An optimum activation concentration of NaOH was introduced to the soil-slag mixture for uniform blending. Specimens were prepared at different mix ratios then left to cure for up to 4 weeks. The unconfined compressive strength test was conducted to monitor the changes in strength at predetermined intervals. It was found that the strength does not necessarily increase with higher steel slag content, indicating an optimum slag content required for the maximum solidification effect to take place. Also, regardless of the slag content, longer curing time produces greater strength gain. In conclusion, steel slag addition to dredged sediments can effectively strengthen the originally weak soil structure by both the “cementation” and “filler” effects, though the combined effects were not distinguished in the present study.